Anti-reflection laminate

A multilayer antireflection laminate with controlled refractive indices and thicknesses addresses colored reflections in optical display devices, achieving low reflectance and high transmittance, enhancing device performance and aesthetics.

JP7612551B2Active Publication Date: 2025-01-14FUKUBI KAGAKU IND
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021164204
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-05
Publication Date
2025-01-14
Estimated Expiration
2041-10-05

AI Technical Summary

Technical Problem

Existing antireflection films exhibit colored reflections and insufficient reflectance characteristics, particularly in optical display devices, necessitating improvements in refractive index layer design and thickness to achieve optimal antireflection performance without coloration.

Method used

A multilayer antireflection laminate comprising specific refractive index layers with controlled refractive indices and thicknesses, including a low refractive index layer with a refractive index of 1.325 to 1.395 and a layer thickness of 92 to 101 nm, a high refractive index layer with 1.750 to 1.790 and 61 to 76 nm, a medium refractive index layer with 1.665 to 1.700 and 70 to 78 nm, and a medium-low refractive index layer with 1.385 to 1.450 and 160 to 217 nm, arranged in a specific order, along with a hard coat layer, to achieve luminous average reflectance of 1.0% or less and transmittance of 98% or more across 380 to 780 nm.

Benefits of technology

The laminate achieves excellent antireflection performance with uncolored reflections, maintaining high transmittance and preventing coloration, suitable for optical display devices and automotive touch panels, ensuring aesthetic appeal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612551000026
    Figure 0007612551000026
  • Figure 0007612551000027
    Figure 0007612551000027
  • Figure 0007612551000001
    Figure 0007612551000001
Patent Text Reader

Abstract

To provide an excellent antireflection laminate that is excellent in antireflection performance, and has reflection light not colored.SOLUTION: The present invention is an antireflection laminate that includes a base material (B), a hard coat layer, and an antireflection membrane (AR) in this order. The antireflection membrane (AR) includes: a low refractive index layer in which a refractive index is 1.325 to 1.395, and a layer thickness is 92 to 101 nm; a high refractive index layer in which the refractive index is 1.750 to 1.790, and the layer thickness is 61 to 76 nm; and a middle refractive index layer in which the refractive index is 1.665 to 1.700, and the layer thickness is 70 to 78nm; and a middle low refractive index layer in which the refractive index 1.385 to 1.450, and the layer thickness is 160 to 217 nm. The respective layers are arranged in order of the middle low refractive index layer, the middle refractive index layer, the high refractive index layer, and the low refractive index layer from a hard coat layer side, and the refractive index of the low refractive index layer is lower than that of the middle low refractive index layer. Visual average reflectance of both surfaces in 380 to 780 nm wavelength is equal to or less than 1.0%, and visual average transmittance in 380 to 780 nm wavelength is equal to or more than 98%. A reflection hue indicated by CIE L*a*b*color system (JIS Z 8781-4:2013) in the low refractive index layer surface is -4≤a*≤5, and -12≤b*≤0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antireflection laminate provided on the surface of a window, a display, etc., in order to prevent reflection of external light. More specifically, the present invention relates to an antireflection laminate provided on the front panel of an optical display device such as an LED display (LED, OLED), a liquid crystal display (LCD), or a plasma display (PDP). [Background technology]

[0002] Patent Document 1 proposes an anti-reflection film consisting of three layers formed by coating on a light-transmitting substrate, each layer having a predetermined thickness. However, the minimum reflectance of this anti-reflection film is about 0.5% at a wavelength of 600 nm, and the maximum reflectance of visible light in the range of 380 to 780 nm is estimated to be several percent. Therefore, there is room for further improvement in order to satisfy the reflectance characteristics required for recent optical display devices. The present inventors previously proposed an antireflection laminate using a multilayer antireflection film consisting of four layers with different refractive indexes, the laminate having an average luminous reflectance of 0.6% or less on both sides for visible light with wavelengths of 380 to 780 nm (Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-182007 A [Patent Document 2] Patent application 2020-072175 Summary of the Invention [Problem to be solved by the invention]

[0004] The invention proposed in Patent Document 2 exhibits low average luminous reflectance on both sides for visible light with wavelengths of 380 to 780 nm and exhibits excellent anti-reflection performance. However, it has been found that there is a problem in which the reflected light is tinted blue or red (coloration), which can reduce the value of the product. The present inventors have conducted extensive research into the cause of coloration and have found that the coloration is related to the refractive index of each refractive index layer, the balance of the refractive indexes, and the thickness of the refractive index layers. They have also found that the refractive index of the medium-low refractive index layers is a particularly important factor, and have found that coloration can be prevented by precisely controlling the refractive index and thickness of each refractive index layer, thereby arriving at the present invention. An object of the present invention is to provide an antireflection laminate which has excellent antireflection performance and does not color reflected light. [Means for solving the problem]

[0005] That is, the present invention provides an antireflection laminate comprising a substrate, a hard coat layer, and an antireflection film in this order, the antireflection film being A low refractive index layer having a refractive index of 1.325 to 1.395 and a layer thickness of 92 to 101 nm; A high refractive index layer having a refractive index of 1.750 to 1.790 and a layer thickness of 61 to 76 nm; A medium refractive index layer with a refractive index of 1.665 to 1.700 and a thickness of 70 to 78 nm; A medium-low refractive index layer having a refractive index of 1.385 to 1.450 and a layer thickness of 160 to 217 nm, Constituting the anti-reflective coating The layers are arranged in the following order from the hard coat layer side: a medium-low refractive index layer, a medium refractive index layer, a high refractive index layer, and a low refractive index layer, and the refractive index of the low refractive index layer is lower than that of the medium-low refractive index layer, The hard coat layer has a thickness of 1 to 3 μm, The antireflection laminate has an average luminous reflectance of 1.0% or less on both sides at wavelengths of 380 to 780 nm, an average luminous transmittance of 98% or more at wavelengths of 380 to 780 nm, and a reflection hue on the surface of the low refractive index layer, as represented by the CIE L*a*b* color system (JIS Z 8781-4:2013), is -4≦a*≦5 and -12≦b*≦0.

[0006] In the above antireflection laminate, 1. The medium-low refractive index layer comprises, relative to 100 parts by mass of a binder component consisting of a mixture of at least one selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof, and (iii) an organic-inorganic hybrid compound: [ka] (wherein R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. [ka] (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; n is 0, 1, or 2. A composition comprising 80 to 350 parts by mass of silica particles and 5 to 15 parts by mass of a metal chelate compound. was hydrolyzed and condensed The composition is made of a cured material. 2. The (iii) organic-inorganic hybrid compound is a hybrid compound having a structure in which an alkoxysilyl group is bonded to a bisphenol A type epoxy compound, a novolak phenol compound, or a polyamic acid compound; 3. The medium refractive index layer is a composition containing 100 parts by mass of at least one binder component selected from the group consisting of the alkoxysilane compound represented by formula (1) (i) or a hydrolysate thereof and the alkoxysilane compound represented by formula (2) (ii) or a hydrolysate thereof, 105 to 140 parts by mass of metal oxide particles, and 1 to 5 parts by mass of a metal chelate compound. was hydrolyzed and condensed The composition is made of a cured material. 4. The high refractive index layer is a composition containing 270 to 430 parts by mass of metal oxide particles and 1 to 10 parts by mass of a metal chelate compound relative to 100 parts by mass of at least one binder component selected from the group consisting of an alkoxysilane compound represented by formula (1) (i) or a hydrolysate thereof and an alkoxysilane compound represented by formula (2) (ii) or a hydrolysate thereof. was hydrolyzed and condensed The composition is made of a cured material. 5. The low refractive index layer is a composition containing 45 to 140 parts by mass of silica particles and 1 to 10 parts by mass of a metal chelate compound, relative to 100 parts by mass of at least one binder component selected from the group consisting of (i) an alkoxysilane compound represented by formula (1) or a hydrolysate thereof and (ii) an alkoxysilane compound represented by formula (2) or a hydrolysate thereof. was hydrolyzed and condensed The composition is made of a cured material. 6. The hard coat layer contains 1 to 30 parts by mass of a silane coupling component, 10 to 80 parts by mass of solid silica particles, and 0.1 to 30 parts by mass of a metal chelate compound, relative to 100 parts by mass of a resin component obtained by curing a trifunctional or lower urethane (meth)acrylate, a tetrafunctional or higher urethane (meth)acrylate, and a (meth)acrylate. is preferred. Effect of the Invention

[0007] The antireflection laminate of the present invention has excellent antireflection properties and light transmittance with respect to visible light. Specifically, in a wide wavelength range of 380 to 780 nm, the average luminous reflectance of both surfaces of the antireflection laminate of the present invention is 1.0% or less, and the average luminous transmittance at wavelengths of 380 to 780 nm is 98% or more. Moreover, a characteristic feature is that coloring of reflected light is prevented. As a result, the reflection hue shown in the CIE L*a*b* color system (JIS Z 8781-4:2013) on the surface of the low refractive index layer is -4≦a*≦5 and -12≦b*≦0. Taking advantage of the above-mentioned properties, the antireflection laminate of the present invention is also useful as a front panel or cover material for a safety sensor, or as an instrument panel or touch panel for an automobile. Since coloring is prevented and light is reflected in a natural color, it is particularly useful for touch panels and meter panels that place importance on design and aesthetics. [Brief description of the drawings]

[0008] [Figure 1] FIG. 4 is a reflectance distribution diagram of the antireflection laminate of Example 2. [Diagram 2] FIG. 2 is a reflectance distribution diagram of the antireflection laminate of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Layer structure of anti-reflection laminate> The antireflection laminate of the present invention is basically composed of a substrate, a hard coat layer, and an antireflection film, which are laminated in this order. The antireflection film is composed of the following components from the hard coat layer side: A low-medium refractive index layer having a refractive index of 1.385 to 1.450 and a layer thickness of 160 to 217 nm; A medium refractive index layer with a refractive index of 1.665 to 1.700 and a thickness of 70 to 78 nm; A high refractive index layer having a refractive index of 1.750 to 1.790 and a layer thickness of 61 to 76 nm; A low refractive index layer with a refractive index of 1.325 to 1.395 and a layer thickness of 92 to 101 nm. The refractive index of the low refractive index layer is set lower than the refractive index of the medium-low refractive index layer. The present invention is characterized by the refractive index and layer thickness of the four refractive index layers that make up the anti-reflection film. In particular, the refractive index of the medium-low refractive index layer is set lower than that of conventional products, and by balancing the respective refractive indices and layer thicknesses, it is possible to achieve both excellent anti-reflection performance and prevention of coloration of reflected light. As long as the antireflection laminate of the present invention has the above-mentioned basic structure, a protective layer may be provided, for example, on the antireflection film (on the viewing side) within a range that does not impair the optical properties described below.

[0010] <Base material> The substrate is preferably made of a transparent resin that has excellent impact resistance and does not impede visibility. The total light transmittance of the substrate at a wavelength of 380 to 780 nm is preferably 88% or more, more preferably 89% or more, and even more preferably 92% or more. From the viewpoint of transparency and impact resistance, the substrate is preferably made of at least one resin selected from the group consisting of acrylic resin, polycarbonate resin, polyethylene terephthalate resin, and triacetyl cellulose resin. A laminated substrate in which these resins are laminated may be used. For example, a laminated substrate of polycarbonate resin and polymethyl methacrylate resin may be used. The thickness of the substrate is designed by appropriately selecting it based on the required transparency and impact resistance, but it is usually in the range of 0.2 to 2.0 mm.

[0011] <Hard coat layer> The hard coat layer is preferably a layer containing a resin component obtained by curing a trifunctional or lower urethane (meth)acrylate and a tetrafunctional or higher urethane (meth)acrylate as main components. The thickness of the hard coat layer is preferably 1 to 3 μm. If the thickness is too thin, it becomes difficult to ensure the basic physical properties (e.g., hardness and strength) of the hard coat layer, and if the thickness is too thick, the difference in physical properties (e.g., flexibility and elongation) from the substrate becomes large, which results in molding defects such as cracks. From this viewpoint, the thickness is preferably 1.2 to 2.5 μm, more preferably 1.5 to 2 μm. The hard coat layer preferably contains a resin component obtained by curing a trifunctional or lower urethane (meth)acrylate and a tetrafunctional or higher urethane (meth)acrylate as main components, a silane coupling component, solid silica particles, and a metal chelate compound.

[0012] (Resin component) The resin component functions as a binder for forming a hard coat layer. As such a binder, it is preferable to use a combination of a trifunctional or less urethane (meth)acrylate and a tetrafunctional or more urethane (meth)acrylate. That is, a trifunctional or less urethane (meth)acrylate forms a relatively flexible part by curing, and a tetrafunctional or more urethane (meth)acrylate forms a hard part by curing, and by using both in combination, a film that is moderately dense and has high hardness can be formed. Furthermore, in order to reduce the viscosity of the binder and improve the coating property, it is preferable to use a normal (meth)acrylate in addition to the above urethane (meth)acrylate.

[0013] In the present invention, the above-mentioned trifunctional or lower urethane (meth)acrylate and tetrafunctional or higher urethane (meth)acrylate are preferably used in a mass ratio of 2 / 98 to 70 / 30, particularly 10 / 90 to 60 / 40. If the amount of trifunctional or lower urethane (meth)acrylate used is too large, the hardness of the obtained hard coat layer may be impaired, and the basic performance of the hard coat layer may be reduced.

[0014] (Silane coupling component) The hard coat layer preferably contains a silane coupling component, which is used to stably disperse and hold the silica particles described below in the hard coat layer without falling off, and at the same time, to ensure adhesion to the anti-reflection film.

[0015] As the silane coupling component, a conventionally known silane coupling agent or a hydrolysate thereof can be used. Specific examples of silane coupling agents include vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyltriacetoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-(N-styrylmethyl-β-aminoethylamino)propyltrimethoxysilane hydrochloride, γ-chloropropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, methyltrichlorosilane, and dimethyldichlorosilane.

[0016] In the present invention, the content of the above silane coupling component in the hard coat layer is set in the range of preferably 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the resin component formed from the above-mentioned urethane (meth)acrylate.

[0017] (Solid Silica Particles) The hard coat layer preferably contains solid silica particles. The solid silica particles in the hard coat layer preferably have an average particle size of 5 to 500 nm and a refractive index in the range of 1.44 to 1.50. By using such particles, basic properties such as hardness can be uniformly imparted to the entire hard coat layer. Hereinafter, the average particle size of the particles refers to the median diameter (d50).

[0018] The content of the solid silica particles is preferably 10 to 80 parts by mass, more preferably 20 to 60 parts by mass, per 100 parts by mass of the resin component formed from the above-mentioned urethane (meth)acrylate, etc. By including such silica particles in the hard coat layer in such a range, it is possible to improve adhesion with the anti-reflection film and effectively prevent cracks, etc., while maintaining the basic properties of the hard coat layer.

[0019] (Metal chelate compounds) The hard coat layer preferably contains a metal chelate compound. The metal chelate compound is used to introduce a crosslinked structure into the hard coat layer and make the hard coat layer denser. Although a crosslinked structure is also formed by the resin component such as the above-mentioned urethane (meth)acrylate, the denseness is reduced by using a low-functional urethane (meth)acrylate to impart flexibility. Metal chelate compounds are used to compensate for the reduced denseness without impairing the flexibility of the hard coat layer, in other words, to adjust mechanical properties such as hardness that are affected by the denseness of the film. In addition, since such a metal chelate compound is also contained in the antireflective film, the use of the metal chelate compound can further improve the adhesion between the hard coat layer and the antireflective film, and can effectively prevent cracks and the like during molding.

[0020] Such metal chelate compounds include compounds of titanium, zirconium, aluminum, etc., which contain ligands. Specific examples of metal chelate compounds include: Titanium chelate compounds such as triethoxy mono(acetylacetonate)titanium, diethoxy bis(acetylacetonate)titanium, monoethoxy tris(acetylacetonate)titanium, tetrakis(acetylacetonate)titanium, triethoxy mono(ethylacetoacetate)titanium, diethoxy bis(ethylacetoacetate)titanium, monoethoxy tris(ethylacetoacetate)titanium, mono(acetylacetonate)tris(ethylacetoacetate)titanium, bis(acetylacetonate)bis(ethylacetoacetate)titanium, and tris(acetylacetonate)mono(ethylacetoacetate)titanium; Zirconium chelate compounds such as triethoxy mono(acetylacetonate)zirconium, diethoxy bis(acetylacetonate)zirconium, monoethoxy tris(acetylacetonate)zirconium, tetrakis(acetylacetonate)zirconium, triethoxy mono(ethylacetoacetate)zirconium, diethoxy bis(ethylacetoacetate)zirconium, monoethoxy tris(ethylacetoacetate)zirconium, tetrakis(ethylacetoacetate)zirconium, mono(acetylacetonate) tris(ethylacetoacetate)zirconium, bis(acetylacetonate) bis(ethylacetoacetate)zirconium, and tris(acetylacetonate) mono(ethylacetoacetate)zirconium; Aluminum chelate compounds such as diethoxy mono(acetylacetonate)aluminum, monoethoxy bis(acetylacetonate)aluminum, di-i-propoxy mono(acetylacetonate)aluminum, monoethoxy bis(ethylacetoacetate)aluminum, diethoxy mono(ethylacetoacetate)aluminum, and tris(acetylacetonate)aluminum; etc.

[0021] The above-mentioned metal chelate compound is used in an amount of preferably 0.1 to 30 parts by mass, more preferably 0.5 to 15 parts by mass, per 100 parts by mass of the resin component formed from the urethane (meth)acrylate, etc. By using it within this range, the hard coat layer can be made denser to improve mechanical properties such as hardness, and the adhesion between the hard coat layer and the anti-reflection film formed on the hard coat layer can be improved.

[0022] (Formation of hard coat layer) The hard coat layer is formed by applying a hard coat layer forming solution containing a monomer or oligomer for forming a resin component onto a substrate to form a coating film, followed by drying as necessary, and then carrying out a polymerization and curing reaction. The hard coat layer forming solution is prepared by dissolving the above components, together with optional components such as a catalytic amount of a polymerization initiator, in the following organic solvent for the purpose of adjusting viscosity and facilitating application.

[0023] Polymerization initiators include chemical polymerization initiators of chemical curing type and photopolymerization initiators of photocuring type, and are used according to the polymerization method of the curing process. Examples of chemical polymerization initiators include peroxides such as benzoyl peroxide, di-t-butyl peroxide, and methyl ethyl ketone peroxide. Examples of photopolymerization initiators include diketones such as benzil and camphorquinone, benzoin or benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; aromatic ketones such as benzophenone, benzoylbenzoic acid, and 1-hydroxycyclohexyl phenyl ketone; benzil ketals such as benzil dimethyl ketal and benzil diethyl ketal; acetophenones such as 2-hydroxy-2-methyl-1-phenyl-propan-1-one and 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one; and anthraquinones such as 2-methylanthraquinone and 2-ethylanthraquinone.

[0024] Suitable organic solvents for use in the solution for forming a hard coat layer include alcohol compounds such as methyl alcohol, ethyl alcohol, propyl alcohol, and isopropanol; aromatic compounds such as toluene and xylene; ester compounds such as ethyl acetate, butyl acetate, isobutyl acetate, and sec-butyl acetate; and ketone compounds such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and diacetone alcohol. The amount of the organic solvent used may be an amount that allows the hard coat layer-forming solution to have a viscosity suitable for coating without causing dripping, etc. The amount of the organic solvent is a value including the amount of the particle dispersion medium such as solid silica particles. The above-mentioned components constituting the hard coat layer forming solution are usually mixed and stirred arbitrarily at around room temperature to form a solution. When using a commercially available particle dispersion, the solvent, which is the dispersion medium, is inevitably mixed into the solution. The solvent in the hard coat layer forming solution and the organic solvent that is separately mixed are removed in the drying and curing process.

[0025] The method of applying the hard coat layer-forming solution onto the substrate is not particularly limited, and methods such as dip coating, roll coating, die coating, flow coating, and spraying can be used. From the viewpoints of appearance quality and layer thickness control, the dip coating method is preferred. Thereafter, the coating is dried, and then heated or irradiated with ionizing radiation such as ultraviolet light or electron beams to cause a curing reaction, thereby forming a hard coat layer.

[0026] <Anti-reflective film> An anti-reflection film is laminated on the hard coat layer, which is a multi-layer anti-reflection film composed of four refractive index layers having the following characteristics: Low refractive index layer: refractive index = 1.325 to 1.395, layer thickness = 92 to 101 nm High refractive index layer: refractive index = 1.750 to 1.790, layer thickness = 61 to 76 nm Medium refractive index layer: refractive index = 1.665 to 1.700, layer thickness = 70 to 78 nm Medium to low refractive index layer: refractive index = 1.385 to 1.450, layer thickness = 160 to 217 nm The refractive index of the low refractive index layer is lower than that of the medium / low refractive index layer, and the four refractive index layers are arranged in the following order from the hard coat layer side: medium / low refractive index layer, medium refractive index layer, high refractive index layer, and low refractive index layer. By using the above four-layer antireflection film, the obtained antireflection laminate has an average luminous reflectance of 1.0% or less on both sides at wavelengths of 380 to 780 nm, an average luminous transmittance of 98% or more at wavelengths of 380 to 780 nm, and a reflection hue on the surface of the low refractive index layer, which is represented by the CIE L*a*b* color system (JIS Z 8781-4:2013), is -4≦a*≦5 and -12≦b*≦0, thereby providing an antireflection product with high optical performance and no coloring.

[0027] [Medium to low refractive index layer] The refractive index of the medium-low refractive index layer is 1.385 to 1.450. If it is less than 1.385, the average luminous reflectance and b* value are insufficient, and if it is designed to exceed 1.450, the ratio of the binder component becomes high, which deteriorates wettability and causes poor appearance of the formed layer. From these viewpoints, it is preferably 1.400 to 1.450, and more preferably 1.420 to 1.450. The thickness of the medium-low refractive index layer is 160 to 217 nm. If it is less than 160 nm, the b* value is insufficient, and if it exceeds 217 nm, the a* value is insufficient. From these viewpoints, the thickness is preferably 160 to 200 nm, and more preferably 165 to 185 nm. The refractive index of the medium-low refractive index layer is set to be higher than that of the low refractive index layer within the above range. The medium-low refractive index layer comprises, relative to 100 parts by mass of a binder component consisting of at least one selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof, and (iii) an organic-inorganic hybrid compound: [ka] (wherein R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. [ka] (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; n is 0, 1, or 2. It is preferable that the composition comprises a cured product of a composition containing 80 to 350 parts by mass of silica particles and 5 to 15 parts by mass of a metal chelate compound.

[0028] (Binder component) It is important that the binder component comprises a mixture of at least one alkoxysilane compound selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof (hereinafter also referred to as an alkoxysilane compound, etc.) and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof (hereinafter also referred to as an alkoxysilane compound, etc.) and (iii) an organic-inorganic hybrid compound.

[0029] (Formula (1) Alkoxysilane Compound, etc.) It is one of the binder components and is represented by the following formula (1). [ka] In the formula, R is an alkylene group. The number of carbon atoms in the alkylene group is preferably 1 to 9, and more preferably 1 to 5. Examples of the alkylene group include a methylene group, an ethylene group, a trimethylene group, a propylene group, a butylene group, a tetramethylene group, a pentylene group, and a hexylene group. R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. The number of carbon atoms in the alkyl group is preferably 1 to 9, and more preferably 1 to 5. Examples of the alkyl group include a methyl group, an ethyl group, a trimethyl group, a propyl group, a butyl group, a tetramethyl group, a pentyl group, and a hexyl group. The number of carbon atoms in the alkoxyalkyl group is preferably 1 to 9, more preferably 1 to 5. Examples of the alkoxy group in the alkoxyalkyl group include a methoxy group, an ethoxy group, a propoxy group, etc. Examples of the alkyl group in the alkoxyalkyl group include a methyl group, an ethyl group, a trimethyl group, a propyl group, a butyl group, a tetramethyl group, a pentyl group, a hexyl group, etc. Examples of halogen atoms include fluorine, chlorine, bromine, and iodine. Specific examples include known compounds such as γ-glycidoxypropyltrimethoxysilane and γ-glycidoxypropyltriethoxysilane. Depending on the type, the alkoxysilane compound of formula (1) is preferably used as a hydrolyzate that has been partially hydrolyzed in advance with a dilute acid or the like for the purpose of improving the solubility in water or a solvent. The method of pre-hydrolysis is not particularly limited, and a method of partially hydrolyzing the alkoxysilane compound by coexisting the alkoxysilane compound with an acid together with other components in a solution for forming a medium-low refractive index layer described later is used.

[0030] (Formula (2) Alkoxysilane Compound, etc.) It is one of the binder components and is represented by the following formula (2): [ka] In formula (2), R 1 is the same as formula (1). n is 0, 1 or 2. R 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group. The number of carbon atoms in the alkyl group is preferably 1 to 9, and more preferably 1 to 5. Examples of the alkyl group include a methyl group, an ethyl group, a trimethyl group, a propyl group, a butyl group, a tetramethyl group, a pentyl group, and a hexyl group. The number of carbon atoms in the alkenyl group is preferably 1 to 9, more preferably 1 to 5. Examples of the alkenyl group include an ethenyl group, a propenyl group, a butenyl group, a pentyl group, and a hexenyl group. The number of carbon atoms in the alkoxyalkyl group is preferably 1 to 9, more preferably 1 to 5. Examples of the alkoxy group in the alkoxyalkyl group include a methoxy group, an ethoxy group, a propoxy group, etc. Examples of the alkyl group in the alkoxyalkyl group include a methyl group, an ethyl group, a trimethyl group, a propyl group, a butyl group, a tetramethyl group, a pentyl group, a hexyl group, etc. Specifically, examples of compounds where n=0 include tetraalkoxysilanes such as tetraethoxysilane and tetramethoxysilane; examples of compounds where n=1 include trialkoxysilanes such as methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxy(ethoxy)silane, and vinyltriethoxysilane; and examples of compounds where n=2 include dialkoxysilanes such as dimethyldimethoxysilane and dimethyldiethoxysilane. The alkoxysilane compound of the formula (2) may also be used as a hydrolyzate that has been partially hydrolyzed in advance, similarly to that of the formula (1).

[0031] (organic / inorganic composite compound) It is an essential component constituting the binder component. By using it in combination with the alkoxysilane compound or the like, it imparts flexibility to the medium to low refractive index layer, suppresses the occurrence of cracks, and contributes to improving chemical resistance and moisture resistance. An organic-inorganic hybrid compound is, for example, a hybrid compound in which an alkoxysilyl group is bonded to a bisphenol A type epoxy compound. Crosslinking of the epoxy groups occurs between the compounds, and silica particles are generated by the sol-gel hardening of the alkoxysilyl groups, resulting in a hardened material that combines the advantages of both organic and inorganic materials and does not have a Tg like glass. The organic-inorganic composite compound includes various types of compounds, for example, composite compounds having a structure in which an alkoxysilyl group is bonded to a bisphenol A epoxy compound, a novolac phenol compound, or a polyamic acid compound, etc. In the present invention, a composite compound in which an alkoxysilyl group is bonded to a bisphenol A type epoxy compound is most suitable from the viewpoints that the medium-low refractive index layer has high elasticity and high alkali resistance, and is easily available. The organic-inorganic composite compound is used in the range of 25 to 50 mass % based on the total binder components, preferably 25 to 35 mass %. If it is less than 25 mass %, the above effect is not exhibited, and if it exceeds 50 mass %, the abrasion resistance tends to deteriorate, which is not preferable.

[0032] (Silica particles) In the medium-low refractive index layer of the present invention, silica particles are used to control the refractive index to 1.385 to 1.450. As the silica particles, two types of silica particles are used: the solid silica particles used in the hard coat layer and the hollow silica particles described below. The hollow silica particles are particles made of silicon dioxide having a cavity inside, and are usually fine hollow particles having an average particle size of 5 to 150 nm and an outer shell thickness of about 1 to 15 nm. Therefore, it is preferable to select hollow silica particles having a refractive index in the range of 1.20 to 1.38. The hollow silica particles are known, for example from JP-A-2001-233611, and are generally commercially available in the form of a dispersion in a lower alcohol such as methanol, ethanol, or propanol. It is therefore preferable to obtain and use a commercially available product. The silica particles are appropriately selected and used from the range of 80 to 350 parts by mass, preferably 55 to 175 parts by mass of the solid silica particles and 25 to 175 parts by mass of the hollow silica particles, relative to 100 parts by mass of the binder component, so as to satisfy the predetermined refractive index. In particular, the inclusion of solid silica particles is preferable in terms of improving the scratch resistance of the medium-low refractive index layer.

[0033] (Metal chelate compounds) The metal chelate compound is a component that functions as a crosslinking agent and makes the refractive index layer formed denser. As the compound, those used in forming the hard coat layer can be used without any restrictions. The metal chelate compound is used in an amount of 5 to 15 parts by mass, preferably 5 to 10 parts by mass, per 100 parts by mass of the binder component. If it exceeds 15 parts by mass, the metal chelate compound tends to precipitate in the low-medium refractive index layer, causing a decrease in anti-reflection performance and a poor appearance. If it is less than 5 parts by mass, the strength and hardness of the low-medium refractive index layer are not improved.

[0034] (Formation of low and medium refractive index layers) The medium-low refractive index layer is formed by dissolving specific amounts of the above-mentioned components, and further optional components, in the organic solvent described below for the purpose of adjusting viscosity and facilitating application to prepare a solution for forming the medium-low refractive index layer, applying this solution onto the hard coat layer, drying it, and then heating and curing it. For forming the medium to low refractive index layer, an appropriate amount of an acid aqueous solution such as an aqueous hydrochloric acid solution may be blended as an optional component in order to promote hydrolysis and condensation of the alkoxysilane compound or the like.

[0035] As the organic solvent used in the solution for forming the medium to low refractive index layer, the same organic solvent as that used in the solution for forming the hard coat layer can be used. The above components constituting the solution for forming the medium-low refractive index layer are usually mixed and stirred at room temperature to form a solution. When a commercially available silica particle dispersion is used, the solvent, which is the dispersion medium, is inevitably mixed into the solution. The solvent in the solution for forming the medium-low refractive index layer and the organic solvent added separately are removed in the drying and curing steps.

[0036] The method of applying the solution for forming the medium-low refractive index layer onto the hard coat layer is not particularly limited, and methods such as dip coating, roll coating, die coating, flow coating, and spraying can be used, as in the case of forming the hard coat layer. However, from the viewpoint of appearance quality and layer thickness control, the dip coating method is preferable. After that, the solution is dried, heated, and heat-cured to form the medium-low refractive index layer. Drying is performed in normal air at 20 to 30°C for 0.05 to 1 hour, and heat-curing is performed in normal air at 60 to 90°C for 0.2 to 1 hour. Note that drying and heat-curing may be performed simultaneously.

[0037] [Medium Refractive Index Layer] The refractive index of the medium refractive index layer is 1.665 to 1.700. If it is less than 1.665, the a* value is insufficient, and if it exceeds 1.700, the a* value is also insufficient. From these viewpoints, the refractive index is preferably 1.670 to 1.695, and more preferably 1.675 to 1.695. The thickness of the medium refractive index layer is 70 to 78 nm. If it is less than 70 nm, the b* value is insufficient, and if it exceeds 78 nm, the b* value is also insufficient. From these viewpoints, the thickness is preferably 71 to 77 nm, and more preferably 72 to 76 nm. The medium refractive index layer is suitably made of a cured product of a composition containing 100 parts by mass of a binder component, 105 to 140 parts by mass of metal oxide particles, and 1 to 10 parts by mass of a metal chelate compound.

[0038] (Binder component) As the binder component, the alkoxysilane compound represented by formula (1) or formula (2) used in forming the medium-low refractive index layer or its hydrolyzate is used without any restrictions for the same purpose. Formulas (1) and (2) are as explained in the section on the medium-low refractive index layer.

[0039] (metal oxide particles) The medium refractive index layer contains metal oxide particles in order to control the refractive index to the predetermined value. Metal oxide particles having a refractive index of 1.50 or more can be used. For example, at least one oxide particle selected from the group consisting of zirconium oxide (refractive index = 2.40), niobium pentoxide, antimony-doped tin oxide (ATO), indium oxide-tin oxide (ITO), phosphorus-doped tin oxide (PTO), fluorine-doped tin oxide (FTO) and antimony pentoxide is preferable. These metal oxide particles are appropriately combined to adjust the desired refractive index. Such particles are known per se and commercially available. The average particle size of the metal oxide particles is preferably 1 to 100 nm, and more preferably 1 to 70 nm. The metal oxide particles are appropriately selected from the range of 105 to 140 parts by mass per 100 parts by mass of the binder component so as to satisfy the above-mentioned predetermined refractive index, taking into consideration the refractive index change due to thermal history, etc. In particular, zirconium oxide particles are preferably used in terms of light resistance.

[0040] (Metal chelate compounds) As the metal chelate compound, the metal chelate compounds used in forming the medium to low refractive index layers can be used without any restrictions for the same purpose. The content of the metal chelate compound in the medium refractive index layer is 1 to 10 parts by mass, preferably 1 to 7 parts by mass, based on 100 parts by mass of the binder component. If it exceeds 10 parts by mass, the metal chelate compound tends to precipitate in the medium refractive index layer, causing a decrease in anti-reflection performance and a poor appearance. If it is less than 1 part by mass, the strength and hardness of the medium refractive index layer are not improved.

[0041] (Formation of medium refractive index layer) The medium refractive index layer is formed by dissolving specific amounts of each of the above components, and further any optional components, in an organic solvent to prepare a solution for forming the medium refractive index layer, applying this solution onto the medium to low refractive index layer, drying it, and then heating it to thermally cure it. The organic solvent used, the mixing order and mixing conditions of the components, as well as the coating method, drying and heating methods, etc. are similar to those used in the formation of the medium to low refractive index layers.

[0042] [High Refractive Index Layer] In order to achieve extremely high antireflection performance, the antireflection film has a high refractive index layer between a medium refractive index layer and a low refractive index layer. The refractive index of the high refractive index layer is 1.750 to 1.790. If it is less than 1.750, the average luminous reflectance is insufficient. In the present invention, the refractive index of the film formed reaches a plateau at 1.790, and it is not possible to design a refractive index that exceeds this value. From these viewpoints, the refractive index is preferably 1.760 to 1.790, and more preferably 1.770 to 1.785. The thickness of the high refractive index layer is 61 to 76 nm. If it is less than 61 nm, the b* value is insufficient, and if it exceeds 76 nm, the b* value is also insufficient. From these viewpoints, the thickness is preferably 63 to 75 nm, and more preferably 66 to 73 nm. The high refractive index layer is suitably made of a cured product of a composition containing 270 to 430 parts by mass of metal oxide particles and 1 to 10 parts by mass of a metal chelate compound per 100 parts by mass of a binder component.

[0043] (Binder component) As the binder component, the alkoxysilane compound represented by formula (1) or formula (2) used in forming the medium-low refractive index layer or its hydrolyzate is used without any restrictions for the same purpose. Formulas (1) and (2) are as explained in the section on the medium-low refractive index layer.

[0044] (metal oxide particles) The high refractive index layer contains metal oxide particles to control the refractive index to the predetermined value. As the metal oxide particles, the metal oxide particles used in forming the medium refractive index layer can be used without any restrictions. The metal oxide particles are appropriately selected from the range of 270 to 430 parts by mass of metal oxide particles per 100 parts by mass of the binder component so as to satisfy the predetermined refractive index. In particular, it is preferable to contain zirconium oxide particles.

[0045] (Metal chelate compounds) As the binder component, the metal chelate compounds used in forming the medium to low refractive index layers can be used without any restrictions for the same purpose. The content of the metal chelate compound in the high refractive index layer is 1 to 10 parts by mass, preferably 2 to 7 parts by mass, based on 100 parts by mass of the binder component. If the content exceeds 10 parts by mass, the metal chelate compound tends to precipitate in the high refractive index layer, causing a decrease in antireflection performance and a defective appearance.

[0046] (Formation of high refractive index layer) The high refractive index layer is formed by dissolving specific amounts of each of the above components, and also any optional components, in an organic solvent to prepare a solution for forming the high refractive index layer, applying this solution onto the medium refractive index layer, drying it, and then heating it to thermally cure it. The organic solvent used, the mixing order and mixing conditions of the components, as well as the coating method, drying and heating methods, etc. are similar to those used in the formation of the medium to low refractive index layers.

[0047] [Low Refractive Index Layer] This is a refractive index layer located on the outermost layer (viewing side) of the antireflection film, and is an essential layer for the antireflection laminate of the present invention to exhibit antireflection performance. The refractive index of the low refractive index layer is 1.325 to 1.395. If it is less than 1.325, the b* value is insufficient, and if it exceeds 1.395, the average luminous reflectance is insufficient. From these viewpoints, it is preferably 1.335 to 1.390, and more preferably 1.345 to 1.385. The thickness of the low refractive index layer is 92 to 101 nm. If it is less than 92 nm, the b* value is insufficient, and if it exceeds 101 nm, the b* value is also insufficient. From these viewpoints, the thickness is preferably 92 to 99 nm, and more preferably 93 to 98 nm. The low refractive index layer is suitably made of a cured product of a composition containing 45 to 140 parts by mass of silica particles and 1 to 10 parts by mass of a metal chelate compound relative to 100 parts by mass of a binder component.

[0048] (Binder component) As the binder component, the alkoxysilane compound represented by formula (1) or formula (2) used in forming the medium-low refractive index layer or its hydrolyzate is used without any restrictions for the same purpose. Formulas (1) and (2) are as explained in the section on the medium-low refractive index layer.

[0049] (Silica particles) In the low refractive index layer, silica particles are used to control the refractive index to 1.325 to 1.395. As the silica particles, the solid silica particles and hollow silica particles used in forming the medium and low refractive index layers can be used without any restrictions. The silica particles are appropriately selected and used in an amount of 45 to 140 parts by mass per 100 parts by mass of the binder component so as to satisfy the predetermined refractive index. In particular, it is preferable to include hollow silica particles in order to achieve a low refractive index. On the other hand, in the case of an anti-reflection film intended for abrasion resistance, it is preferable to use solid silica particles that do not have a cavity inside in combination.

[0050] (Metal chelate compounds) As the binder component, the metal chelate compounds used in forming the medium to low refractive index layers can be used without any restrictions for the same purpose. The content of the metal chelate compound in the low refractive index layer is 1 to 10 parts by mass, preferably 3 to 10 parts by mass, based on 100 parts by mass of the binder component. If the content exceeds 10 parts by mass, the metal chelate compound tends to precipitate in the low refractive index layer, causing a decrease in antireflection performance and a defective appearance.

[0051] (Formation of low refractive index layer) The low refractive index layer is formed by dissolving specific amounts of each of the above components, and further optional components, in an organic solvent to prepare a solution for forming the low refractive index layer, applying this solution onto the high refractive index layer, drying it, and then heating it to thermally cure it. The organic solvent used, the mixing order and mixing conditions of the components, as well as the coating method, drying and heating methods, etc. are similar to those used in the formation of the medium to low refractive index layers.

[0052] <Characteristics of anti-reflection laminate> [Average visual reflectance on both sides] The antireflection laminate of the present invention has a luminous average reflectance (hereinafter also referred to as luminous average reflectance) of both surfaces at wavelengths of 380 to 780 nm of 1.0% or less, preferably 0.8% or less, and more preferably 0.6% or less. As is clear from a comparison of the reflectance distribution of the antireflection laminate of Example 2 shown in FIG. 1 with the reflectance distribution of the antireflection laminate of Comparative Example 1 shown in FIG. 2, the antireflection laminate of the present invention exhibits low reflectance over a wide wavelength range. [Luminous average transmittance] The average luminous transmittance of the antireflection laminate of the present invention at wavelengths of 380 to 780 nm is 98% or more, and preferably 99% or more. [Reflection Hue] The reflection hue, as represented by the CIE L*a*b* color system (JIS Z 8781-4:2013), on the surface of the low refractive index layer of the antireflection laminate of the present invention is -4≦a*≦5 and -12≦b*≦0. The reflected hue indicated by the CIE L*a*b* color system is a physical property indicating the hue of the reflected light of the low refractive index layer of the antireflection laminate of the present invention, where a* indicates the red direction, -a* direction indicates the green direction, b* direction indicates the yellow direction, and -b* direction indicates the blue direction, and when this value is within the range of -4≦a*≦5 and -12≦b*≦0, it indicates that the reflected light is colorless and transparent. EXAMPLES

[0053] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Furthermore, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention. The various components, abbreviations and test methods used in the following Examples and Comparative Examples are as follows.

[0054] ((Meth)acrylates) Bifunctional acrylate: Triethylene glycol diacrylate Trifunctional acrylate: Urethane acrylate with three acrylate groups at the end Hexafunctional acrylate: urethane acrylate with pentaerythritol triacrylate (Silane coupling agent) γ-GPS: 3-glycidoxypropyltrimethoxysilane (Binder component) γ-GPS: 3-glycidoxypropyltrimethoxysilane Organic / inorganic composite compounds: ASE: Bisphenol A type epoxy compound modified with trialkoxymethylsilyl group (alkoxy group-containing silane-modified epoxy compound) Dispersion solvent: Diethylene glycol dimethyl ether (DGDE) (Metal chelate compounds) AlTA: Aluminum tris(acetylacetonate) (Silica particles) Hollow Silica Particles Average particle size: 60 nm, refractive index: 1.30, solid content: 20% by weight, Dispersion solvent: IPA Solid Silica Particles Average particle size: 7 nm, refractive index: 1.45, solid content: 20% by weight, Dispersion solvent: IPA (metal oxide particles) Zirconium oxide particles Average particle size: 24 nm, refractive index: 2.40, solid content: 15% by weight, Dispersion solvent: A mixture of normal butyl alcohol (NBA) and ethyl alcohol (EA) liquid (Photopolymerization initiator) HCHP: 1-hydroxycyclohexyl phenyl ketone MMMP: 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (UV absorber) BTA: Benzotriazole-based UV absorber (hydrolysis catalyst) HCl: 0.05N hydrochloric acid (Organic solvent) IPA: Isopropyl alcohol Ethacol: Ethyl alcohol and isopropyl alcohol mixture NPA: Normal propyl alcohol SBAC: acetic acid s-butyl ester MIBK: Methyl isobutyl ketone

[0055] [Refractive index of each layer] The solutions for forming each layer were applied onto an acrylic substrate and cured to form each refractive index layer. The refractive index was then calculated from the reflectance of each layer by adjusting the peak of the reflection spectrum to 550 nm using a JASCO V-570 UV-Visible Spectrophotometer.

[0056] [Thickness of each layer] The layer thickness was determined by simulation using the reflectance spectrum obtained from the actual measurement of spectroscopic data.

[0057] [Average visual reflectance on both sides] The average luminous reflectance of both surfaces was measured by the following method: Using a JASCO V-570 UV-Visible Spectrophotometer, the spectral reflectance was measured at 380 nm to 780 nm, and calculated by multiplying it by a weighting coefficient based on JIS Z 8722.

[0058] [Luminous average transmittance] The average luminous transmittance was measured by the following method: Using a JASCO V-570 UV-Visible Spectrophotometer, the spectral transmittance was measured at 380 nm to 780 nm, and calculated by multiplying it by a weighting coefficient based on JIS Z 8722.

[0059] [Reflection hue] Measurements were taken at wavelengths from 380 nm to 780 nm using a JASCO V-570 UV-Visible Spectrophotometer. The reflection hue indicated by the CIE L*a*b* color system was calculated based on JIS Z 8781-4:2013.

[0060] <Solution for forming hard coat layer> The components shown in Table 1 below were mixed in the amounts shown in Table 1 to prepare a solution for forming a hard coat layer (HC-1).

[0061] [Table 1]

[0062] <Solution for forming anti-reflection film> (Solution for forming low and medium refractive index layers) The components shown in Table 2 below were mixed in the amounts shown in Table 2 to prepare solutions for forming medium to low refractive index layers (ml-1 to ml-4).

[0063] [Table 2] (Solution for forming medium refractive index layer) The components shown in Table 3 below were mixed in the amounts shown in Table 3 to prepare solutions (m-1 to m-5) for forming a medium refractive index layer.

[0064] [Table 3]

[0065] (Solution for forming high refractive index layer) The components shown in Table 4 below were mixed in the amounts shown in Table 4 to prepare solutions for forming high refractive index layers (h-1 to h-4).

[0066] [Table 4] (Solution for forming low refractive index layer) The components shown in Table 5 below were mixed in the amounts shown in Table 5 to prepare solutions (l-1 to l-5) for forming low refractive index layers.

[0067] [Table 5]

[0068] Example 1 A hard coat layer and an anti-reflective film were formed in this order on a 1 mm thick polymethyl methacrylate (PMMA) substrate by the following method. The layer thickness was adjusted by the withdrawal speed from the dipped forming solution for each layer.

[0069] [Formation of hard coat layer] The substrate was dipped in the hard coat layer forming solution (HC-1), then dried at 60°C for 8 minutes, and then cured with ultraviolet light at 500 mJ to obtain a laminate in which a hard coat layer having a thickness of 1.7 μm was formed on the substrate.

[0070] [Formation of anti-reflection film] On the above laminate, a medium to low refractive index layer, a medium refractive index layer, a high refractive index layer and a low refractive index layer were formed by the following procedure. The laminate was dipped in a solution for forming a medium-low refractive index layer (ml-2), and then dried at 90° C. for 15 minutes to form a semi-cured medium-low refractive index layer having a thickness of 175 nm on the substrate. It is considered that the medium-low refractive index layer is in an insufficiently cured state (semi-cured) due to drying under the above conditions, and the same applies to each of the following layers. Next, the laminate was dipped in a medium refractive index layer forming solution (m-2) and then dried at 90°C for 15 minutes to form a semi-cured medium refractive index layer with a layer thickness of 75 nm on the semi-cured medium-low refractive index layer. Next, the laminate was dipped in a high refractive index layer forming solution (h-2) and then dried at 90°C for 15 minutes to form a semi-cured high refractive index layer with a layer thickness of 70 nm on the semi-cured medium refractive index layer. Next, the laminate was dipped in a low refractive index layer forming solution (l-1) and then dried at 90° C. for 15 minutes to form a semi-cured low refractive index layer with a layer thickness of 95 nm on the semi-cured high refractive index layer. The laminate formed by laminating the above semi-cured antireflection film on the hard coat layer was cured with ultraviolet light at 500 mJ and then heated at 90° C. for 6 hours to allow the curing to proceed sufficiently, thereby producing an antireflection laminate of the present invention. The average luminous reflectance, average luminous transmittance and reflection hue of both sides of the obtained antireflection laminate were measured according to the above-mentioned methods and are shown in Table 8. The solution used, the refractive index and the layer thickness of each layer are shown in Table 6.

[0071] Examples 2 to 17 Antireflection laminates were produced in the same manner as in Example 1, except that the refractive index layer-forming solutions and hard coat layer-forming solutions were used in the combinations shown in Tables 6 and 7. The average luminous reflectance, average luminous transmittance, and reflection hue of both sides of the obtained antireflection laminate were measured according to the above-mentioned methods and are shown in Table 8. The solutions used, refractive index, and layer thickness of each layer are shown in Tables 6 and 7. Figure 1 shows the reflectance distribution of the antireflection laminate obtained in Example 2.

[0072] [Table 6]

[0073] [Table 7]

[0074] [Table 8]

[0075] Comparative Examples 1 to 14 Antireflection laminates were produced in the same manner as in Example 1, except that the refractive index layer-forming solutions and hard coat layer-forming solutions were used in the combinations shown in Tables 9 and 10. The average luminous reflectance, average luminous transmittance, and reflection hue of both sides of the obtained antireflection laminate were measured according to the above-mentioned methods and are shown in Table 11. The solutions used, refractive index, and layer thickness of each layer are shown in Tables 9 and 10. Figure 2 shows the reflectance distribution of the antireflection laminate obtained in Comparative Example 1.

[0076] [Table 9]

[0077] [Table 10]

[0078] [Table 11]

[0079] Comparative Example 1 is a case where the refractive index of the low refractive index layer is high, and the average luminous reflectance is poor. Comparative Example 2 is a case where the refractive index of the low refractive index layer is low, and the b* value is greater than 0, resulting in yellow coloration. Comparative Example 3 is a case where the refractive index of the high refractive index layer is low, and the average luminous reflectance is poor. In Comparative Example 4, the refractive index of the medium refractive index layer was high, the a* value was less than -4, and the sample was colored blue-green. In Comparative Example 5, the refractive index of the medium refractive index layer was low, the a* value was more than 5, and the sample was colored reddish purple. In Comparative Example 6, in which the refractive index of the medium-low refractive index layer was low, not only was the average luminous reflectance poor, but the b* value was greater than 0 and the film was colored yellow. In Comparative Example 7, the low refractive index layer had a large thickness, and the b* value was less than -12, resulting in a blue color. The average luminous reflectance was poor. In Comparative Example 8, the low refractive index layer had a small thickness, and the b* value was more than 0, resulting in a yellow color. In Comparative Example 9, the high refractive index layer was thick, the b* value was greater than 0, and the sample was colored yellow. In Comparative Example 10, the high refractive index layer was thin, the b* value was less than −12, and the sample was colored blue. In Comparative Example 11, the thickness of the intermediate refractive index layer was large, the b* value was greater than 0, and the sample was colored yellow. In Comparative Example 12, the thickness of the intermediate refractive index layer was small, the b* value was less than −12, and the sample was colored blue. In Comparative Example 13, the medium to low refractive index layers were thick, the a* value was less than -4, and the sample was colored blue-green. In Comparative Example 14, the medium to low refractive index layers were thin, the b* value was more than 0, and the sample was colored yellow.

Claims

1. An antireflection laminate comprising a substrate, a hard coat layer, and an antireflection film in this order, the antireflection film comprising: A low refractive index layer having a refractive index of 1.325 to 1.395 and a layer thickness of 92 to 101 nm; A high refractive index layer having a refractive index of 1.750 to 1.790 and a layer thickness of 61 to 76 nm; A medium refractive index layer having a refractive index of 1.665 to 1.700 and a layer thickness of 70 to 78 nm; and a low-to-medium refractive index layer having a refractive index of 1.385 to 1.450 and a layer thickness of 160 to 217 nm, the layers constituting the antireflection film being arranged in the following order from the hard coat layer side: low-to-medium refractive index layer, medium refractive index layer, high refractive index layer, and low refractive index layer, and the refractive index of the low refractive index layer is lower than that of the low-to-medium refractive index layer, The hard coat layer has a thickness of 1 to 3 μm, The antireflection laminate has an average luminous reflectance of 1.0% or less on both sides in the wavelength range of 380 to 780 nm, an average luminous transmittance of 98% or more in the wavelength range of 380 to 780 nm, and a reflection hue on the surface of the low refractive index layer, as shown in the CIE L*a*b* color system (JIS Z 8781-4:2013), is -4≦a*≦5 and -12≦b*≦0.

2. The medium-low refractive index layer contains, per 100 parts by mass of a binder component consisting of a mixture of at least one selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof, and (iii) an organic-inorganic hybrid compound: 【Chemistry 1】 (Wherein, R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. 【Chemistry 2】 (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; and n is 0, 1, or 2.

2. The anti-reflection laminate according to claim 1, which comprises a cured product obtained by hydrolysis and condensation of a composition containing 80 to 350 parts by mass of silica particles and 5 to 15 parts by mass of a metal chelate compound.

3. 3. The antireflection laminate according to claim 2, wherein the organic-inorganic hybrid compound (iii) is a hybrid compound having a structure in which an alkoxysilyl group is bonded to a bisphenol A type epoxy compound, a novolak phenol compound, or a polyamic acid compound.

4. The medium refractive index layer contains, per 100 parts by mass of at least one binder component selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof: 【Chemistry 3】 (Wherein, R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. 【Chemistry 4】 (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; and n is 0, 1, or 2.

2. The anti-reflection laminate according to claim 1, which comprises a cured product obtained by hydrolysis and condensation of a composition containing 105 to 140 parts by mass of metal oxide particles and 1 to 10 parts by mass of a metal chelate compound.

5. The high refractive index layer contains, per 100 parts by mass of at least one binder component selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof: 【Chemistry 5】 (Wherein, R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. 【Chemistry 6】 (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; and n is 0, 1, or 2.

2. The anti-reflection laminate according to claim 1, which comprises a cured product obtained by hydrolysis and condensation of a composition containing 270 to 430 parts by mass of metal oxide particles and 1 to 10 parts by mass of a metal chelate compound.

6. The low refractive index layer contains, per 100 parts by mass of at least one binder component selected from the group consisting of (i) an alkoxysilane compound represented by the following formula (1) or a hydrolysate thereof, and (ii) an alkoxysilane compound represented by the following formula (2) or a hydrolysate thereof: 【Chemistry 7】 (Wherein, R is an alkylene group, R 1 is an alkyl group, an alkoxyalkyl group, or a halogen atom. 【Chemistry 8】 (In the formula, R 1 R is an alkyl group, an alkoxyalkyl group, or a halogen atom. 2 is an alkyl group, an alkenyl group, or an alkoxyalkyl group; and n is 0, 1, or 2.

2. The anti-reflection laminate according to claim 1, which comprises a cured product obtained by hydrolysis and condensation of a composition containing 45 to 140 parts by mass of silica particles and 1 to 10 parts by mass of a metal chelate compound.

Citation Information

Patent Citations

  • Durable reflection preventing film

    JP2002182007A

  • Anti-reflection film

    JP2006079067A

  • Coil component

    JP2020072175A

  • Reflective, pigmented, or color-shifting, scratch-resistant coatings and articles

    JP2020519948A

  • Anti-reflection film and method for manufacturing the same

    US20130078440A1